Using Code-Switching as A Strategy for Improving Classroom Interaction at SMKN 1 Enrekang Regency - Musdalifah, Musdalifah (Majesty Journal, 2020)
The main objective of this research that was to known about what were types and the functions of code-switching used by English teachers, and what were factors cause the English teachers to use code-switching in classroom interaction at SMKN 1Enrekang regency. This research employed a descriptive qualitative design and purposive sampling technique. The participant of this research that was an English teacher at SMKN 1 Enrekang regency. The participant consisted of 3 English teachers who belong to three grades. There were some instruments were used to collect the data in this research namely observation, interview, questionnaire, and triangulation. The main findings of this research that was the English teachers of SMKN 1 Enrekang regency known types and functions of code-switching in classroom interaction, and know some factors cause they must to use code-switching in classroom interaction.